IMPLEMENTASI KURIKULUM BERBASIS DISTINGSI DALAM PENGEMBANGAN KARAKTER RELIGIUS DI MI NU HIDAYATUN NAJAH - Rustyawati, Dian; Fauzi, M.; Amin, Fathul (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The development of the world of information technology and easy access to social media is a challenge for educational institutions. Easy access to information technology raises many problems for children, such as addiction to gadgets, lack of communication skills, and even affects children's ethics and behavior. The vulnerability of a moral crisis makes educational institutions a stronghold to shape student character and instiAbstractll religious values. For this reason, it is necessary to have a curriculum that is able to answer the needs and in accordance with the vision and mission of the institution. The problems raised in this study are the implementation of the Special Curriculum at MI NU Hidayatun Najah and the Development of the Special Curriculum in shaping religious character at MI NU Hidayatun Najah. The method used in this research is field research with a qualitative approach. Based on the results of the study, it is known that the implementation of the Special Curriculum is carried out to support the development of students' religious understanding as well as the distinction of the Institute. There are also local contents in the Special Curriculum, namely Alqur'an and memorization, madrasah diniyah, SKUA, and akhlakul karimah. The development of this distinctive curriculum is carried out on an ongoing basis based on the results of curriculum evaluation. This research has limitations in the research area, namely MI NU Hidayatun Najah Tuban, so that the research results cannot be generalized. Future research can examine more specifically each program or companion book used in the implementation of a typical curriculum at MI NU Hidayatun Najah.